Report on Characteristics of Control Valves - SURENDRA KUMAR, RAJESH KUMAR S, MANOJ KUMAR S, RAM SUBHAG S, SUNIL KUMAR S, S RASHID ALI nad GOVARDHAN T (1994)
INTERNAL GUIDE: RAMARAJAN V, MVJCE
Keywords: Control Valves